FRAGMENTED NARRATIVES, UNIFIED STRUGGLES: THE SUBALTERN IN 'THE MINISTRY OF UTMOST HAPPINESS' BY ARUNDHATI ROY (Contemporary Journal of Social Science Review, 2025)
Post-colonial theory has remained one of the most appealing academic topics of study since the Indian subcontinent gained independence from colonial rule. The term "subaltern" is a product of the post-colonial era, which has given rise to a vast body of literature. The definition and features connected with the term "subaltern" have changed dramatically as a result of socioeconomic conditions. Arundhati Roy, a conscious writer, has focused her second novel, “The Ministry of Utmost Happiness”, on contemporary socio-political issues that are pertinent to the study of "subaltern," particularly in the South Asian context. As the work is dedicated to "The Unconsoled," it is essentially about everyone and everything happening in quickly changing India, notably about displaced and marginalised people . Transgender issues were raised by the protagonist or primary character of the literature. Other persistent issues such as gender discrimination, caste inequity, capitalism, and a slew of other sociopolitical issues were also addressed. S Roy is a prolific author who has written works on capitalism, globalization, and democracy. As a result, The Ministry of Utmost Happiness is definitely and instinctively an explosion of the author's observations of "The New Subaltern" who are victims of social and political injustice. As a result, the purpose of this article is to look at Roy's portrayal of "The New Subaltern" in a democratic India setting through her characters, who are framed in a post-colonial position.